PHARMACOVIGILANCE IN CLINICAL RESEARCH: PAST, PRESENT AND FUTURE - Chauhan, Pratibha; Yadav, Ashish; Kirodian, Babita (International Journal of Drug Regulatory Affairs, 2018)
The growing clinical research after the product patents rights for the pharmaceutical industries as per the trade related aspects of intellectual property rights agreement and adverse drug reaction monitoring of the marketed drugs have raised many ethical and regulatory issues regarding the promotion of new drugs in Indian markets. It becomes vital to understand the history, growth and evolution of the regulatory aspects of drugs which are handled by multiple Ministries and Departments of the Government of India. Although amendment to Schedule Y, registration of Ethics committee, registration of Clinical Trials, Speeding up review process, Pharmacovigilance (PhV) programme for India and Inspection of clinical trial sites have been started by the various regulatory agencies. India’s growing partaking in multinational trials, this artifact explores potential areas of Indian pharmacovigilance, requiring reform and provides recommendations for building a robust safety reporting system. (1) Despite global focus on Development Safety Update Report, local regulators are not yet insistent on real-time update of a drug’s cumulative safety profile. Issues like reporting requirements for generic trials, pregnancy reporting and lenient timeline for death/life-threatening events need attention. (2)